2019
DOI: 10.1021/acs.iecr.9b00227
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Equilibria Modeling of Fast Pyrolysis Bio-Oils. Group Contribution Associating Equation of State Extension to Lignin Monomers and Derivatives

Abstract: Fast pyrolysis is a promising route to using biomass as a source of renewable energy and chemicals. For economic feasibility, this process has to be optimized with regard to product yield and handling. One of the big challenges in detailed process design is the complexity of biomass derived liquid mixtures, since they comprise hundreds of different organo-oxygenated chemicals, such as alcohols, ketones, aldehydes, furans, sugar derivatives, and also aromatic components if lignocellulosic biomass is processed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…5,42−44 Thus, FPBO is composed of molecules with very different molecular masses and polarities, which probably control the CO 2 solubility of FPBO. Due to this peculiarity, FPBO can be viewed from two contrasting positions: FPBO can be considered as a mixture of rather small molecules, as it happens in model mixtures, 45,46 or, alternatively, FPBO can be described by its high molecular weight components. Close to the last position are approaches used to explain the solubility in polymers.…”
Section: Co 2 Solubility In Fpbo Mixturesmentioning
confidence: 99%
“…5,42−44 Thus, FPBO is composed of molecules with very different molecular masses and polarities, which probably control the CO 2 solubility of FPBO. Due to this peculiarity, FPBO can be viewed from two contrasting positions: FPBO can be considered as a mixture of rather small molecules, as it happens in model mixtures, 45,46 or, alternatively, FPBO can be described by its high molecular weight components. Close to the last position are approaches used to explain the solubility in polymers.…”
Section: Co 2 Solubility In Fpbo Mixturesmentioning
confidence: 99%
“…A relevant challenge met when modeling fast pyrolysis, including the condensation of fast pyrolysis volatiles, is the physicochemical characterization of the compounds found in the model. ,, Westerhof et al demonstrated this when they predicted the effects of condensation conditions on fractions of light compounds using a simple equilibrium stage model. Westerhof et al also previously compared an equilibrium flash condensation model with experimental results when they studied the control of the water content in FPBO.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the vapor–liquid equilibrium (VLE) requires the user to choose a thermodynamic model, and Carlson recommends the use of activity coefficient models to model mixtures rich in non-ideal components. Many of the components of pyrolysis condensates lack model parameters in databases or in the literature; therefore, the use of group-contribution models, such as modified UNIFAC Dortmund (UNIFAC-DMD) and the group contribution with association equation of state (GCA-EoS), is favorable. Both models have been reported to be reliable tools for predicting phase equilibria (including FPBO condensation processes) over wide temperature ranges and have seen numerous applications in research and industry. ,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to distillation, fractional condensation is another separation method considered in conceptual designs and experimental setups [10]. The available literature on multiphase equilibria for the fast pyrolysis bio-oils was partially considered recently [15]. The main idea of that paper was to extend the group-contribution associating equation of state to lignin derivatives.…”
Section: Introductionmentioning
confidence: 99%